2023
DOI: 10.12688/materialsopenres.17525.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of barely visible impact damage carbon fibre reinforced epoxy composite using ultrasound method

Abstract: Background: Carbon fibre reinforced epoxy (CFRP) is susceptible to impact damage which could resulted in reduction of the mechanical properties. This paper studies the architecture of barely visible impact damage (BVID) to comprehend the extent of damage on quasi-isotropic CFRP laminates of varying thickness (i.e. 16, 24 and 32-ply laminates of 3, 4 and 5 mm respectively). Methods: Quasi-static indentation is chosen to produce BVID on CFRP laminates, followed by using non-destruction evaluation method, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although the QSI test resulted in barely visible damage to the specimens (i.e., 16-and 24-ply laminates), the size of the subsurface damage in the 24-ply laminate was about two times that of the 16-ply laminate. [30] This was not surprising given that the amount of impact energy needed to create the BVID in the former was higher than the latter. In addition, with regard to the morphology of the subsurface damage at the front and rear surface as seen from the thermal images, it was concluded that the damage could prevail across several laminas, which is consistent with findings from other reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the QSI test resulted in barely visible damage to the specimens (i.e., 16-and 24-ply laminates), the size of the subsurface damage in the 24-ply laminate was about two times that of the 16-ply laminate. [30] This was not surprising given that the amount of impact energy needed to create the BVID in the former was higher than the latter. In addition, with regard to the morphology of the subsurface damage at the front and rear surface as seen from the thermal images, it was concluded that the damage could prevail across several laminas, which is consistent with findings from other reports.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with regard to the morphology of the subsurface damage at the front and rear surface as seen from the thermal images, it was concluded that the damage could prevail across several laminas, which is consistent with findings from other reports. [21,30,31] Altogether, these may have practical implications during inspection: for a given barely visible damage observed at the impacted surface, the subsurface damage in a thick laminate could be much more extensive compared to a thin laminate. [30] T A B L E 5 An orthogonal array L 12 (mixed-level design) of Taguchi with the repair efficiency derived based on the mechanical properties of the CFRP laminates in repaired state to pristine state (η P ) and repair efficiency derived based on the residual mechanical properties between the repaired and damage states and between the pristine and damaged states (η D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation